Investigation of Local Mechanical Properties of Al-Cu-Li Alloys by Acoustic Microscope - Berezina, Sofia; Kolosov, Oleg; Slabeycius, Juraj (Communications - Scientific letters of the University of Zilina, 2003)
The reflected scanning acoustic microscope was used for investigation of elastic properties of extruded Al-Cu-Li alloys. The local sound velocity and attenuation were measured by the V(z) curve method. The results show strong anisotropy of material due to extrusion of the sample.